RETRACTION HB, G., Ardiyanto, S. Y., Nurkadri, N., Novita, N., Widiyanto, W. E., Setyawan, H., Putro, B. N., Harmanto, H., Darmawan, A., & Radulovic, N. (2024). Garantizar la equidad y la transparencia en el deporte mediante el respeto de los principios jurídicos y las normas éticas (Ensuring fairness and transparency in sports through compliance to legal principles and ethical standards). Retos, 60, 204–216. https://doi.org/10.47197/retos.v60.108935 - RETOS, RETOS (Retos, 2025)
HB, G., Ardiyanto, S. Y., Nurkadri, N., Novita, N., Widiyanto, W. E., Setyawan, H., Putro, B. N., Harmanto, H., Darmawan, A., & Radulovic, N. (2024).  Garantizar la equidad y la transparencia en el deporte mediante el respeto de los principios jurídicos y las normas éticas (Ensuring fairness and transparency in sports through compliance to legal principles and ethical standards). Retos, 60, 204–216. https://doi.org/10.47197/retos.v60.108935Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that the authorship of the article has been manipulated. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were needed. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. Likewise, a large number of citations and references were manipulated. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 10Authors in the published PDF with modified authors: 10Differences between the authors between both moments: +5 y -5 (Additions: Nurkadri, Novita, Wahyu Eko Widiyanto, Harmanto, Nikola Radulovic. Eliminated: Zulbahri Zulbahri, Francesca Latino, Francesco Tafuri, Özgür Eken, Ratko Pavlovic)